(untitled) (Economic Journal of Nepal, 2013)
The agriculture sector had effectively been kept out of the multilateral trading system established through the GATT in 1947. This anomaly was rectified during the Uruguay Round Negotiations, culminating in the formation of WTO in 1995, when multilateral disciplines were introduced in the agricultural sector. The WTO Agreement on agriculture seeks to improve market access and to reduce trade distorting subsidies in agricultural products. India has been arguing for the introduction of a regime which provides adequate protection to the domestic sensitivities in the agricultural sector. The greatest achievement acclaimed through media by the UPA 1&2 governments was the lifting of 140 million people out of poverty in the last 10 years. This has a strong bearing and implication on the agriculture policy pursued in India and the question of inclusiveness. This paper attempts a critical evaluation and discussion of the agricultural policy in India over the decades and its pro-activeness towards inclusiveness.